2008
DOI: 10.1080/08860220701857134
|View full text |Cite
|
Sign up to set email alerts
|

Strong Correlation of B2-Microglobulin (B2-m) with Procalcitonin (PCT) in the Serum of Chronic Hemodialysis Patients: A Role for Infections in the Dialysis-Related Amyloidosis?

Abstract: Introduction. Infections trigger the activation of defensive cells capable to produce and release B 2 -microglobulin (B 2 -m). Procalcitonin (PCT), secreted by a wide range of human cells, included the aforementioned defensive cells, is generally considered a sensitive and specific marker of infection. In this prospective study, we examined the possibility that infections, as detected by increased levels of PCT, increase the serum levels of B 2 -m in chronic hemodialysis (CHD) patients, possibly affecting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
(40 reference statements)
0
7
0
1
Order By: Relevance
“…A diagnostic index with good sensitivity and specificity is highly essential in clinical settings to detect intracranial infection and guide clinicians to take necessary interventions, improve the prognosis of patients, and reduce the hospitalization time and economic burden. PCT has been widely studied in recent years for the early diagnosis of bacterial infection severity, treatment effect, disease prognosis and as reference for antibiotic use (24 26). …”
Section: Discussionmentioning
confidence: 99%
“…A diagnostic index with good sensitivity and specificity is highly essential in clinical settings to detect intracranial infection and guide clinicians to take necessary interventions, improve the prognosis of patients, and reduce the hospitalization time and economic burden. PCT has been widely studied in recent years for the early diagnosis of bacterial infection severity, treatment effect, disease prognosis and as reference for antibiotic use (24 26). …”
Section: Discussionmentioning
confidence: 99%
“…The concentration of beta-2 microglobulin in plasma and other body fluids increases in proportion to lost kidney function, as it is normally eliminated by the process of glomerular filtration followed by reabsorption and catabolism by the proximal tubular cells. Blumberg et al [30] reported correlation of beta-2 microglobulin with dialysis vintage, whereas beta-2 microglobulin production and tissue accumulation enhance the rate of progression of dialysis-related amyloidosis [31]. In our study, the significant correlation of plasmatic calprotectin with beta-2 microglobulin and with dialysis vintage could be explained by the increased time-dependent production and secretion of cytokines due to blood contact with bio-incompatible parts of HD membranes and the relevant impact of infections that activate immunocompetent cells.…”
Section: Discussionmentioning
confidence: 99%
“…β2-microglobulin is considered as a prototypical middle molecule and is traditionally used as a marker of middle molecule removal. Both in pre-dialysis CKD and in dialysis patients [ 22 ], β2-microglobulin has been associated with several deleterious outcomes like pro-inflammatory processes [ 23 ], as well as with vascular stiffness [ 24 ], bone remodelling [ 25 ] or cognitive dysfunction [ 26 ]. Cytokines are another kind of middle molecule that show increased circulating concentrations along with the decline of renal function.…”
Section: Introductionmentioning
confidence: 99%